Assisted reproductive technology in Japan: A summary report for 2016 by the Ethics Committee of the Japan Society of Obstetrics and Gynecology. (29th November 2018) - Ishihara, Osamu; Jwa, Seung Chik; Kuwahara, Akira; Ishikawa, Tomonori; Kugu, Koji; Sawa, Rintaro; Banno, Kouji; Irahara, Minoru; Saito, Hidekazu
Abstract: Purpose: The Japan Society of Obstetrics and Gynecology started an online cycle‐based assisted reproductive technology (ART) registry system in 2007. This report presents the characteristics and treatment outcomes of ART registered for the cycles practiced during 2016. Methods: Cycle‐specific information for all ART cycles implemented in participating ART facilities were collected. A descriptive analysis was conducted for the registry database of 2016. Results: In total, 447 790 treatment cycles and 54 110 neonates (one in 18.1 neonates born in Japan) were reported in 2016. The mean patients' age was 38.1 years (SD = 4.5). Among the egg retrieval cycles, 104 575 of 251 399 (41.6%) were freeze‐all cycles without fresh embryo transfers (ET), while fresh ET was performed in 64 497 cycles (58.4%). A total of 187 132 frozen‐thawed ET cycles were reported, resulting in 62 432 pregnancies and 44 484 neonates born. Single ET was selected for 81.0% of fresh transfers and 82.7% of frozen cycles, resulting in singleton pregnancy/live birth rates of 97.0%/96.4% and 96.7%/96.4%, respectively. Conclusion: The total ART cycles and subsequent live births continued to increase in 2016. Single ET was performed more than 80%, and ET has shifted from using fresh embryos to frozen ones.